Some New Characterizations of Parallel Factorable Surface in Riemannian Three Dimensional Heisenberg Group - Suroğlu, Gülden Altay (My University, 2018)
In this paper, we give some properties of parallel factorable surface which is obtained by group operations inRiemannian three dimensional Heisenberg Group H?. Then, we obtain some characterizetions of parallel factorablesurface according to Levi- Civita connections of H?.
Keywords: Matematik